A study on nucleation kinetics of carbamazepine-fumaric acid form B cocrystal: article - Mohd Zawawi, Mohamad Zulhelmi; Anuar, Nornizar; Abd Rahim, Syarifah; Shukri, Umi Rafiah (2017)
Cocrystallization is a common technique selected by many researchers in purpose to enhance pharmaceutical drugs properties and nucleation kinetics is one of the important parameter to perform cocrystallization. However, the nucleation kinetics for carbamazepine-fumaric acid form B cocrystal has not been studied. The purpose of this experiment is to study on nucleation kinetics of CBZ-FUM acid form B by using Nývlt’s approach. In this study, carbamazepine (CBZ) was selected as API and fumaric acid (FUM) was used as coformer in order to produce CBZ-FUM form B cocrystal. To ensure form B was produced, stoichiometric ratio of 1:2 of CBZ to FUM was used in this study. Metastable zone width (MSZW) was studied by manipulating the solution concentration in range from 0.0467 g/mL to 0.0512 g/mL. Besides that, the effect of cooling rate on MSZW also was studied by varying the cooling rate (0.10, 0.25, 0.50, and 0.75 ˚C/min). Based on results obtained, the MSZW was increased as cooling rate increases but concentration has insignificant effect on MSZW. The nucleation rate obtained was in range of 0.1325 to 1.3052. Cocrystal also undergoes characterization process by using FTIR microscopy and optical microscope. Based on FTIR results, cocrystal peaks was formed at above and below of pure component peaks. For XRPD result, it shows that CBZ-FUM form B cocrystal has developed 5 new peaks in between 6.6˚ and 34˚ 2θ. Meanwhile, peaks on DSC result between range 185 ˚C and 186.5 ˚C were proved the formation of form B polymorph. Lastly, CBZ-FUM form B cocrystal that formed has needle-liked morphology.